2001
DOI: 10.1038/sj.bmt.1702822
|View full text |Cite
|
Sign up to set email alerts
|

Infectious complications after high-dose chemotherapy and autologous stem cell transplantation: comparison between patients with lymphoma or multiple myeloma and patients with solid tumors

Abstract: patients (66 with solid tumor, 36 with lymphoma, 14 with multiple myeloma, one with acute leukemia) underwent 178 cycles of high-dose chemotherapy and autologous stem cell transplantation (ASCT) at our institution. We retrospectively analyzed the infectious complications that occurred after ASCT. Median duration of neutropenia (granulocyte count Ͻ0.5 × 10 9 /l ) was 8 days, the overall incidence of fever requiring antimicrobial treatment was 63%. 35.4% of patients had fever of unknown orign (FUO), whereas prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
39
2
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(56 citation statements)
references
References 19 publications
8
39
2
7
Order By: Relevance
“…17 In a study of infectious complications in patients with multiple myeloma who were receiving high-dose therapy, primary bacteremia was seen in 21.3%. 18 Fatal infections occurred in 2.6%. A second study reported that infections were documented in 30% of patients with myeloma after peripheral blood progenitor cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…17 In a study of infectious complications in patients with multiple myeloma who were receiving high-dose therapy, primary bacteremia was seen in 21.3%. 18 Fatal infections occurred in 2.6%. A second study reported that infections were documented in 30% of patients with myeloma after peripheral blood progenitor cell transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Infections are very common during this treatment: up to 80% of patients have fever, and more than one third suffer from well-defined infections. [9][10][11] These numbers are based on quite small series of patients. A closer description of infectious toxicity is not seen in the large prospective trials of ASCT.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The rate of infectious complications increases with the duration of neutropenia. 3 There are several possibilities to shorten the pancytopenic period after autologous transplantation.…”
mentioning
confidence: 99%